Individualisierte Therapie der chronischen lymphatischen Leukämie - von Tresckow, Julia; Hallek, Michael; Eichhorst, Barbara (DMW - Deutsche Medizinische Wochenschrift, 2018)
Because of the excellent prognosis in early asymptomatic stage of the disease all patients outside clinical trial should undergo “watch & wait” independently of their individual risk profile. Prognostic markers and scoring systems, as the CLL international prognostic index (CLL-IPI), help predicting the individual prognosis. In advanced stage disease standard frontline therapy in patients without high risk factors is still the combination of chemotherapy and CD20-antibody. However, particularly elderly patients with unfavorable prognostic factors may alternatively be treated with the Btk-inhibitor. Novel targeted agents are the treatment of choice in presence of high risk prognostic factors as well as in most relapsed situations. They are currently tested in currently ongoing trials in frontline.
Keywords: Chronische lymphatische Leukämie (CLL); Chemo-Immuntherapie; zielgerichtete Substanzen